Edukasi Tentang Pengelolaan Sampah Rumah Tangga Dalam Menjaga Kesehatan Lingkungan Kelurahan Manisa - Maran, Albertus Ata; Alim, Andi; Marpaung, Mauritz Pandapotan; Nurhaedah, Nurhaedah; Pannyiwi, Rahmat; Rahmat, Rezqiqah Aulia (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Waste is a material that is discarded or discarded, which is the result of human or natural activities which is no longer used because its main elements or function have been taken away. Every human activity must generate waste or garbage. Sources of waste can come from households, agriculture, offices, companies, hospitals, markets and so on. Survey method by conducting observations at target locations and conducting interviews about community behavior in terms of managing waste and maintaining environmental cleanliness. The results of the evaluation of the counseling process showed that participants followed the counseling until completion and the counseling was carried out calmly and safely.